PRINCIPAL-AGENT RELATIONSHIPS AND INFORMATION ASYMMETRIES IN FIDUCIARY RISK MANAGEMENT. - Sumaila, Mutiatu (2017)
Abstract. This study was conducted to address the problem of agency relationship and how it is caused by information asymmetry. It identifies the problems and proposes some solutions to them. We also talk about decision making for others with the help of some case studies using various methods of choosing but find all of them to be highly flawed and propose an effective method that can be used. The use of algebra is employed to explain the concept better. Results show that outcomes from choices that yield more utility are those decisions made when a person is free from any distortion of the mind and decisions are made based on what the agent would want, looking at the choice from the future and not the present.